Pelatihan Pembuatan Bio Herbal Dalam Menunjang UMKM Desa Pembuang Hulu II - Maulana Azis; Emie Hayati; Maulina Rosyita Sari; Maulana Maulana; Melisa Melisa; Muhammad Fahrizal; Wehdawati Wehdawati (Indonesia Bergerak : Jurnal Hasil Kegiatan Pengabdian Masyarakat, 2024)
This service, which has been carried out by real work course (KKN) students, explains the process of making Bio Herbal in Pembuang Hulu II Village, Hanau District, Seruyan Regency. This service aims to provide and foster new enthusiasm for the people of Pembuang Hulu II Village in carrying out entrepreneurial activities or MSMEs by providing training in making Bio Herbal by explaining the steps in marketing activities that can be carried out so that in the future it can become a provision for the community or that already in running their business optimally, apart from that, also to find out how Real Work Lecture (KKN) students have an influence on improving the standard of living and welfare of the people of Pembuang Hulu II Village, Hanau District, Seruyan Regency. The method used by KKN students as the implementing team is to use skills, knowledge and mentoring training methods for training participants who have an interest in continuing to develop the results of the training up to the marketing stage. The impact resulting from training in making Bio Herbal can be a new, sustainable opportunity and can become a characteristic of the Pembuang Hulu II Village community.